Traumatic Occupational Hand Injury: Severity, Impairment, Disability and Return to Work - Suttinark, Piyachart (Journal of Health Science of Thailand, 2017)
A descriptive study was performed in the patients presenting with acute traumatic occupational hand injuries that were admitted to Nopparatra-jathanee hospital from January 2009 to December 2009 to demonstrate characteristic and rate of their severity of injury, impairment, disability and return to work. The severity of injury was graded by the use of Hand Injury Severity Score (HISS). After the treatments, the impairment and disability were assessed by the use of the American Medical Association (AMA) guide and the Disabilities of the Arm, Shoulder and Hand (DASH) score and the return to work within 6 months was observed. There were 62 patients that consisted of 52 males and 10 females with an average age of 33 (range 18 to 57, SD 9.5). The average HISS was 80.4 (range 4 to 410, SD 82). Most of the patients had some impairment and disability at a rate of 87 percent and 92 percent. The average of impairment was 7.9 percent (range 0 to 33, SD 8) of the body and the average of disability was 27 percent (range 0 to 68.4, SD 19.6).Some impairment and disability were found in every case of severe to major injury subgroup (score >50). The rate of return to work within 6 months was 93.5 percent and all cases in mild to moderate injury subgroup (score ≤ 50) could return to their work. However not every case could return to their routine and the patients in severe to major injury subgroup (score >50) could return to their normal work at a rate of 54.8 percent. It seems that the severity of injury has some effect on impairment, disability and return to work.